Considérations ontogénétiques et phylogénétiques concernant l’origine de la parole - Louis-Jean Boë; Jean Granat; Jean-Louis Heim; Jean-Luc Schwartz; Pierre Badin; Guillaume Barbier; Guillaume Captier; Antoine Serrurier; Nicolas Kielwasser (Revue de Primatologie)
The end of the XXth century and the beginning of this century saw a reorganization of the researches in the field of speech and language emergence (SLE). Naturalism is the kernel of this new approach. It consists in describing the relations between biological aspects (in every sense of the word) on the one hand and speech and language, on the other hand, by an accumulation of hypotheses and evidence derived from a huge range of data collected thanks to interdisciplinary collaborations.As is the case for researches on the origin of Man, a theoretical profusion of hypotheses has arisen which sometimes leads to very hypothetical developments, based on fragile results and on too little data, and proposed in related but not fully mastered or too much simplified disciplines. This is why regular critical overviews do not seem superfluous. First, we propose a classification (push and pull theory) that provides a new reading of the various theories which have been proposed for half a century. In the present state of knowledge it is not possible to infer when our ancestors acquired the FacultyofSpeechandLanguageandSpeech: control of speech articulators, coordination between larynx and vocal tract, phonology, syntax, semantic and recursivity. Among old unsolved questions: Why is our species alone in having speech and language? Many others questions are (for the moment?) ill posed problems: we do not have sufficiently data to answer. Perhaps these questions will remain unsolved. But we think that the following question can be solved: If we suppose that our ancestors (and distant cousins) controlled their larynx and vocal tract in the same way as present-day humans, did the geometry of their vocal tract allow them to produce the universal sound structures of the languages spoken today? We analyzed 31 skulls from now to 1.5 Ma (millions years) BP (Before Present) for fossil hominids available at the Muséedel’Homme in Paris or in the literature: (1) 10-30 ka BP: modern humans: Paleolithic; (2) 90-200 ka BP: anatomically modern humans; (3) 45-90 ka BP: Neanderthals; (4) 1.5 Ma BP: Homoergaster; These skulls are all well kept and possess a jaw in the majority of cases but the vertebral column has been reconstituted. We attempt to: (1) Localize hyoid bone and then glottis position; (2) Reconstitute a vocal tract model in a plausible way using an articulatory model; (3) Quantify the acoustic capabilities of this reconstituted vocal tract. For this purpose, we combine phylogenesis and ontogenesis. We are in a position to state that our ancestors and distant cousins were equipped with a vocal tract that could produce the same variety of vowel sounds as we can today: the vowels /i a u/. The vocal tract morphology has been favorable to the emergence and production of speech since several hundreds of thousands of years. But how to know to what extent they mastered the control skills needed to produce speech? New lines of research are proposed in which orofacial abilities necessary to the emergence of speech are linked to a precursor mechanism dedicated to feeding (masticating-swallowing movements).